The role of non-suicidal self-injurious behavior on stress regulation in patients with current and remitted Borderline personality disorder - Willis, Franziska (Universitätsbibliothek Heidelberg, 2019)
Borderline personality disorder (BPD) is characterized by disturbed affect regulation as well as disturbed emotion regulation, impulse control, interpersonal interaction and a profoundly disturbed self-image. Subjective levels of high aversive inner tension represent one of the main symptoms of this disease. 60-80% of all BPD patients show non-suicidal self-injurious behavior (NSSI). One of the major motives for NSSI is to cope with these states of high aversive inner tension. Interestingly, the majority of patients use tissue injuring methods. Previous studies have shown that in an experimental setting a small incision with a scalpel led to tension decrease in BPD patients. However, it is unclear what mechanisms underlie this phenomenon and whether the effect is rather due to tissue injury or pain perception or a combination of both. Furthermore, it is unclear to what extent states of aversive inner tension still exist in patients with remitted BPD and if pain perception still plays a role in stress regulation. In order to test the influence of tissue injury independently of pain perception, we investigated 57 female patients with current BPD and 60 healthy female controls. After 30 minutes of stress induction, either a small incision with a scalpel, a non-invasive nociceptive stimulus, in previous studies rated equally painful than the incision, or a non-invasive non-nociceptive tactile stimulus was applied to the right forearm. Throughout the study, subjective and objective stress parameters were recorded. As an immediate effect of stimulus application, we observed a greater decrease pf subjective tension ratings after the two painful stimuli compared to the control stimulus in current BPD patients. However, there was no difference in tension reduction between invasive and non-invasive pain stimulus among BPD patients. We performed the same examination in 30 female remitted BPD patients, to which 30 healthy controls and 30 current BPD patients were matched from the group described above. Here, the results showed that at the beginning of the measurement, the highest tension levels were found in current BPD patients, followed by remitted BPD patients, and the lowest tension ratings were found in healthy controls. During stress induction, patients with current BPD developed a stronger urge for NSSI than remitted BPD patients. In addition, the application of painful stimuli led to a greater decrease of subjective tension ratings in current compared to remitted BPD patients and healthy controls. No correlation between pain perception and stress regulation could be found in both remitted BPD patients and healthy controls. The results show that pain experience or nociceptive stimuli respectively, lead to a reduction of tension levels in patients with current BPD. However, we could not find any evidence for a larger decrease of tension levels due to tissue injury. With regard to remitted BPD patients, the results suggest a fading association between nociception and tension relief, as well as for a reduced presence of urge for NSSI, and for a normalization of pain evaluation.
Keywords: Hochschulschrift